Modern American Trust Act - HIGUCHI, Norio (Institutional Knowledge at Singapore Management University, 2005)
This book is a translation of the "Modern American Trust Act" published by the Japanese publisher Yoshin-do in 2002. This book contains a comparative legal perspective on Japanese trustees of Japanese law. Therefore, this book can give readers of our country an opportunity to understand Japanese law and American law together. The laws of the United States, the federal state, are not the same in every state. However, this situation is not only inefficient in law operation, but also causes high cost structures in some cases. To overcome this phenomenon, the Uniform Code or Uniform Act is enacted, and UCC (Uniform Commercial Code) is the representative one. There was also a standard law enactment work in the field of trust law. It was enacted in 2000 and the subject of this book is the Uniform Trust Code. However, this is not the first standard law on trust law. In 1936, the Uniform Trusts Act was enacted. However, the discipline was so insufficient that the discipline of the trust relationship was not sufficient. Thus, the discipline of trust relationships was left to the legislation or precedent of each state. Over time, there has been a significant change in the trust system in the United States. In addition to the quantitative aspect that the frequency of use of the trust system in the trading system has increased, there has been a qualitative change as well as the rapid dissemination of the trust that can be withdrawn as a method to replace the will. There are also many cases where trust relationships are managed not only within one state but across different states. Each state's Trust Act did not have the content and framework to effectively respond to these changes. The restatement was the restatement of the state law (mainly the Second Restatement Act of 1959 and the Third Restatement Act of 1990). However, these restatements have also revealed limitations. The second restatement was adopted too long ago, so many things did not match the reality of the transaction, and the third restatement only covers the obligations of the trustee. In this context, the modernization and unification of the Trust Act began, and the result of the work was the Uniform Trust Code (UTC) enacted in 2000. The Standard Trust Code is designed to provide "accurate, comprehensive, and easily accessible guidance to each state on the various matters of the Trust Act." The standard trust code is based on many of the state's trust laws, and it is known that the California trust law has the greatest impact.